Inward FDI in small country vs institutional quality of big country - Masron, Tajul Ariffin; Abdul Wahab, Effiezal Aswadi; Niaz Ahmad, Mohd Naseem (2015)
China and India has been well recognized as poor in corruption index, which is one of crucial institutional quality (IQ) elements, but successfully attracted huge FDI inflows. This really sparks our interest on whether the success of these two big countries is followed by other big countries such as Brazil and Russia. Our second related interest is to understand whether the success of these countries in luring FDI inflows is in the expense of other small countries surrounding the region. Finally, if with poor IQ, big countries are still able to attract huge amount of FDI, can IQ in small countries help to boost FDI inflows into small countries. Examining all four regions in which all big countries are located, namely Latin America, Transition Economies, South Asia and South East Asia, this study found that IQ is necessary but not a sufficient condition to lure FDI.